Retranslation in Terms of Film and TV Adaptations: Case of Sherlock Holmes - Cemal Topçu (İstanbul Üniversitesi Çeviribilim Dergisi)
So far the research on retranslation has mainly dealt with literary texts. However, this paper problematizes film and TV adaptations as types of retranslations and aims to reveal the motives of frequent Sherlock Holmes readaptations and discuss them with the ones that are relevant to literary retranslations. Sherlock Holmes (2009), Sherlock Holmes: A Game of Shadows (2011), Sherlock (2010), Elementary (2012), Mr. Holmes (2015), and Holmes & Watson (2018) have been chosen to form a corpus. This study will analyze the strategies adopted by each readaptation and the differences between them. The methodology developed by Peridikaki (2017) for observing shifts between a source text and its adaptation is used with changes to adjust it to this study, which excludes the source material and discusses the film readaptations on their own. Furthermore, based on Inez Okulska’s (2016) arguments, the transmedial process of Sherlock (2010) will be presented as a form of re-iteration. This study argues that just as retranslations of a work improve its position in the literary world, film and TV readaptations and their tie-in products as re-iterations can strengthen the position of an adapted work in media.